2020
DOI: 10.3390/cells9091929
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Notch-Receptor-Mediated Transmission of a Transient Signal into Permanent Information via CRISPR/Cas9-Based Genome Editing

Abstract: Synthetic receptor biology and genome editing are emerging techniques, both of which are currently beginning to be used in preclinical and clinical applications. We were interested in whether a combination of these techniques approaches would allow for the generation of a novel type of reporter cell that would recognize transient cellular events through specifically designed synthetic receptors and would permanently store information about these events via associated gene editing. Reporting cells could be used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 25 publications
(48 reference statements)
3
8
0
Order By: Relevance
“…When analysing transgene expression within single samples, we found that mCherry distribution follows a bimodal on/off response, indicative of the presence of receiver cells which do not interact with sender cells at low sender:receiver cell ratios. This bimodal pattern of transgene induction is also evident in data from Cantz and colleagues (Sgodda et al, 2020). The ability of individual sender cells to induce mCherry induction in STC receiver cells (as seen in Movies 1 and 3) implies that this system can be effectively employed to study the effect of interactions between receiver cells and individual and/or rare sender cells in relevant model systems.…”
Section: Discussionsupporting
confidence: 67%
See 4 more Smart Citations
“…When analysing transgene expression within single samples, we found that mCherry distribution follows a bimodal on/off response, indicative of the presence of receiver cells which do not interact with sender cells at low sender:receiver cell ratios. This bimodal pattern of transgene induction is also evident in data from Cantz and colleagues (Sgodda et al, 2020). The ability of individual sender cells to induce mCherry induction in STC receiver cells (as seen in Movies 1 and 3) implies that this system can be effectively employed to study the effect of interactions between receiver cells and individual and/or rare sender cells in relevant model systems.…”
Section: Discussionsupporting
confidence: 67%
“…We generated sender cell lines expressing high and uniform levels of extracellular membrane-tethered EGFP. This transgenic construct was previously used for SynNotch sender cells (Morsut et al, 2016; Sgodda et al, 2020), and comprises EGFP fused to an N-terminal mouse IgGK signal sequence and a C-terminal human PDGFRB transmembrane domain. The addition of HA and Myc tags at the N- and C-termini of EGFP did not affect the ability of sender cells to induce mCherry expression in STC receiver cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations